Literature Review of Areas of Application of Supply Chain Management in Construction Industry - Nkolika J Peter; Hilary I Okagbue; Chukwuemeka O Iroham; Akunnaya P Opoko; Adedotun O Akinola (International Journal of Supply Chain Management, 2020)
Construction projects are becoming increasingly complex and the conventional methods of managing them have plateaued over the years. The complexity could be traced to the complexity of designs, which requires inputs from different suppliers/contractors. This has led to fragmentation where suppliers/ contractors specialize in a given project and are contracted to deliver only on their area of expertise. The aim of this paper is to produce evidence of the areas of application of supply chain management (SCM) in the construction industry. The aim was achieved by a thorough literature review of works done in the area. The results showed that all the selected research on the SCM falls within eight major areas. They are procurement, logistics, models application, information, performance evaluation, customer relationship, environmental management and sustainability. Other subfields can be derived from the areas.